Le paysage à l’épreuve de la complexité : les raisons de l’action paysagère - Evelyne Gauché (Cybergeo)
The multiplicity of approaches for understanding “landscape” and the polysemy of the term attest to the complexity of landscape as a notion. This article argues that these different approaches reveal and represent different dimensions of a same object, dimensions that hang together in a systemic way and produce landscape as a “complex”. The landscape-complex is a multidimensional object generated through permanent interactions between material, representational and praxeological dimensions. It is concurrently a material object, an object of multiple representations and an object of action. Thus, after explaining the concept of the 'landscape complex' and the three subsystems which compose it, this article will highlight its operating and functional characteristics using Europe as an example. It will illustrate how the interaction of the three subsystems enables us to understand the logic of policies for managing landscapes in Europe.